Vitamin D supplementation ameliorates arthritis but does not alleviates renal injury in pristane-induced lupus model - Eduarda Correa Freitas; Thaís Evelyn Karnopp; Jordana Miranda de Souza Silva; Rafaela Cavalheiro do Espírito Santo; Thales Hein da Rosa; Mayara Souza de Oliveira; Fabiany da Costa Gonçalves; Francine Hehn de Oliveira; Pedro Guilherme Schaefer; Odirlei André Monticielo (Taylor & Francis Group, 2019)
Systemic lupus erythematosus (SLE) is a multifactorial and autoimmune inflammatory disease with pleomorphic clinical manifestations involving different organs and tissues. The study of different murine models has provided a better understanding of these autoimmune phenomena. Pristane-induced lupus represents a suitable model to study factors that could influence the induction and/or progression of SLE, including genetic factors. The objective of the present study was to evaluate the development and evolution of SLE after vitamin D supplementation in PIL model. Here, we evaluated the effects of vitamin D supplementation in model of pristane-induced SLE in female BALB/c mice. The animals were randomly divided into three groups: control group (CO), pristane-induced lupus group (PIL) and pristane-induced lupus group plus vitamin D (VD). Lupus was induced in PIL and VD groups using pristane. PIL group showed arthritis and kidney injury, characterized by increased proteinuria, glomerular mesangial expansion and inflammation. Moreover, PIL model showed increased levels of IL-6, TNF-α and IFN-γ in serum. We observed that treatment with vitamin D improved arthritis through reduced of incidence and arthritis clinical score and edema, but does not influenced renal injury. Treatment with vitamin D was not able to reduce proteinuria levels, decrease mesangial hypercellularity or IgG and IgM deposition in the kidney. Vitamin D supplementation did not alter IL-6, TNF-α, IL-2 and IL-4, but reduce IFN-γ. These results support that the role of vitamin D may be different depending on acting site, what could explain different responses according clinical phenotype. Therefore, further investigations of vitamin D are needed to explore the supplement dosage, timing, and the molecular basis in SLE.